PENINGKATAN KUALITAS PELAYANAN PADA CV. X SELAMA PANDEMI COVID-19 MENGGUNAKAN INSTRUMEN SERVICE QUALITY DAN METODE KANO - Abdurrahman Shiddiq Thaha; Djoko Pitoyo; Inayati Nasrudin; Nurwathi Nurwathi (Gapenas Publisher, 2022)
In COVID-19 pandemic, there are a lot of industries that are affected and required to adapt with the new situation. CV. X is one of the education service providers that focus on language, English language in particular, that is located in Bandung. CV. X needs to satisfy its costumers by giving a good service quality. This research intends to figure out the service quality in CV. X and conducting a service improving action using SERVQUAL instrument and Kano method. To perceive the customer satisfaction, SERVQUAL instrument is used by calculating the gap between costumer expectation and company performance. Kano method is used to categorize which attributes that are required to be improved, sustained and put attention. The result of this research implies that from 5 dimensions of service quality, all of them have not fully met the satisfaction of CV. X customers because there are 17 out of 18 attributes that have negative value which means they have not satisfied customer’s expectation. Based on SERVQUAL calculation and Kano method, it is recommended for 2 attributes to be improved, 5 attributes to be sustained and 7 attributes to be put attention. Whereas. After conducting the service improving action, there is an improvement on service quality for 12 attributes and deterioration on service quality for 6 attributes.